Cognitive behavioural treatment of insomnia in individuals with persistent persecutory delusions: a pilot trial. - Myers, E; Startup, H; Freeman, D (2011)
BACKGROUND AND OBJECTIVES: Insomnia is a putative causal factor for persecutory thinking. Recent epidemiological studies show a strong association of insomnia and paranoia. The clinical implication is that reducing insomnia will reduce paranoid delusions. This study, evaluating for the first time the treatment of insomnia in individuals with persecutory delusions, provides a test of this hypothesis. It was predicted that a brief cognitive behavioural intervention for insomnia (CBT-I) for individuals with persistent persecutory delusions and sleep difficulties would not only reduce the insomnia but that it would also reduce the paranoia. METHODS: Fifteen patients with persistent persecutory delusions and insomnia in the context of a psychotic disorder were each individually given a standard-format, four-session CBT-I intervention. Outcome assessments were conducted at pre-treatment, post-treatment and one-month follow-up. RESULTS: There were no missing data. Following the intervention, significant reductions were found in levels of insomnia and the persecutory delusions. The effect sizes were large, and the changes were maintained at the follow-up. At least two-thirds of participants made substantial improvements in insomnia and approximately half showed substantial reductions in the persecutory delusions. There were also reductions in levels of anomalies of experience, anxiety and depression. LIMITATIONS: The main limitations are the absence of a control group and unblinded assessments. A more methodologically rigorous evaluation of this intervention is now warranted. CONCLUSIONS: These preliminary findings suggest that CBT-I can be used to treat insomnia in individuals with persecutory delusions and that, consistent with the hypothesised causal role, it also lessens the delusions.